Adult Wilms′ tumour - Patil, Tushar; Patel, Kirti V; Shukla, Shilin; Parikh, Bharat; Anand, Asha; Shah, Mithun (Indian Journal of Medical and Paediatric Oncology, 2008)
Wilms′ tumour is most common malignant renal tumour of childhood. Rarely, it may be seen in the adults. We report a 35 year old male presenting with flank pain. Abdominal CT scan revealed a right renal mass and a clinical diagnosis of renal cell carcinoma was made. Nephrectomy was performed, and a final diagnosis of adult Wilms′ tumour was made. This case in being reported on account ot its rarity. Pertinent literature is being reviewed.